New records and observations to the Characean flora (Charales, Charophyceae) of Sicily (Italy) - Romanov R.; Napolitano T.; Van De Weyer K.; Troia A. (Webbia, 2019)
New records to the Characean flora of Sicily are presented. Five species (Chara baltica, C. conimbrigensis, C. oedophylla, Nitella gracilis, Tolypella salina) are new to Sicily, two of them being also new to Italy (Chara conimbrigensis, C. oedophylla). Two species are confirmed for Sicily (Chara aspera, Nitella opaca), three (Chara braunii, C. canescens, Nitella capillaris) are rare taxa. The Characean flora of Sicily, updated with these records, currently includes 25 species, distributed in four genera: Chara (13 species), Nitella (eight species), Tolypella (three species) and Lamprothamnium (one species).